Semiotic Analysis of The Short Story (A Mother Whose Child Is Kidnapped) by Seno Gumira Ajidarma with Charles Sanders Pierce's Theory - Diana Romdhoningsih; Mahpudoh Mahpudoh; Lutfiyah Lutfiyah; Irma Nurmala Dewi; Sri Sukmawati (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2023)
Penelitian ini bertujuan untuk menganalisis cerpen